(untitled) (gjstudies, 2017)
The integrity of financial reporting represents a cornerstone of capital marketefficiency and investor confidence. Within corporate governance structures, audit committees bear primary responsibility for overseeing financial reportingprocesses and ensuring the accuracy of disclosed information. While extant literature has established correlations between certain audit committee attributesand financial reporting outcomes, the underlying mechanisms and complex interactions remain inadequately understood. Traditional approaches have predominantly employed linear models examining isolated characteristics such ascommittee size, meeting frequency, and financial expertise, often yielding inconsistent findings across studies. This research addresses these limitations byintroducing a multidimensional analytical framework that captures the dynamicinterplay between audit committee characteristics and their collective impact onfinancial reporting quality